Evolutionary Analysis of Four Recombinant Viruses of the Porcine Reproductive and Respiratory Syndrome Virus From a Pig Farm in China - Liu, Jiankui; Lai, Liling; Xu, Ye; Yang, Yuan; Li, Jiarui; Liu, Chen; Hunag, Cuiqin; Wei, Chunhua (Frontiers in Veterinary Science, 2022)
The porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogens causing substantial economic losses to the Chinese swine industry. In this study, we analyzed the complete genome sequences of four PRRSV isolates (PRRSV2/CN/SS0/2020, PRRSV2/CN/SS1/2021, PRRSV2/CN/L3/2021, and PRRSV2/CN/L4/2020) isolated from a single pig farm from 2020 to 2021. The genomes of the four isolates were 14962–15023 nt long, excluding the poly (A) tails. Comparative analyses of the genome sequences showed that the four isolates shared 93.2%-98.1% homology, and they had no close PRRSV relatives registered in GenBank (<92%). Furthermore, PRRSV2/CN/SS0/2020 and PRRSV2/CN/SS1/2021 had characteristic 150-aa deletions (aa481+aa537-566 +aa628–747) that were identical to the live attenuated virus vaccine strain TJM-F92 (derived from the HP-PRRSV TJ). Further analysis of the full-length sequences suggests that the four isolates were natural recombinant strains between lineages 1 (NADC30-like), 3 (QYYZ-like), and 8.7 (JXA1-like). Animal experiment revealed discrepancies in virulence between PRRSV2/CN/SS0/2020 and PRRSV2/CN/L3/2021. The strain with high homology to HP-PRRSV demonstrates higher pathogenicity for pigs than the other isolate with low homology to HP-PRRSV. Taken together, our findings suggest that PRRSVs have undergone genome evolution by recombination among field strains/MLV-like strains of different lineages.